PENERAPAN MODEL PEMBELAJARAN QUANTUM TEACHING UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA POKOK BAHASAN STOIKIOMETRI DI KELAS X SMA NEGERI 2 PEKANBARU - Annisa Safitri; Elva Yasmi; Rasmiwetti Rasmiwetti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Research on application of learning model of Quantum Teaching has been done to know the improvement of learning achievement of learners on stoichiometric subject in class X SMA Negeri 2 Pekanbaru. Form of research conducted is experimental research with pretest-posttest design. This study was conducted on the even semester of the academic year 2017/2018. The sample consists of two classes of class X MIPA 2 as the experimental class chosen at random after the normality test and homogeneity test. The experimental class is the treated class by applying the Quantum Teaching learning model. Data analysis technique used is t-test. Based on the results of final data processing using t-test formula obtained thitung> ttable (2.47> 1.67) means the application of learning model Quantum Teaching can improve student achievement in class X MIPA SMA Negeri 2 Pekanbaru. Keywords: Quantum Teaching, Learning Achievement, stoichiometric